Preoperative Removal of Patient Body Jewellery - Porteous, Joan (Operating Room Nurses Association of Canada Journal, 2002)
In today’s society more individuals are wearing body jewellery. In the operating room we have seen an increase in the number of patients arriving with body piercing. The general public is often unaware of risks associated with wearing jewellery during surgery. Not only do we need to educate patients, we also need to educate nurses so that they can knowledgeably discuss, with their patients, the risks associated with wearing body jewellery to the OR. This risk is making body-jewellery a ‘hot topic‘ in most surgical departments today.